PENGARUH KUALITAS, CITRA DAN MEREK TERHADAP LOYALITAS DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING PADA PENGGUNA LAYANAN KARTU PRABAYAR IM3 ( Studi Pada Mahasiswa FISIP Universitas Diponegoro Semarang ) - Anisa Anggraini; Ari Pradhanawati; Hari Susanta Nugraha (Universitas Diponegoro, 2013)
Developments in the world of telecommunications is also accompanied by the competition among telecommunication companies. One of the drivers of loyalty is customer satisfaction factors, which support customers stay using IM3. Loyalty is influenced by many factors including quality, image, and brand. The research was conducted on IM3 prepaid card user at the Faculty of Social and Political Sciences University of Diponegoro. A decline in sales, as well as consumer unloyalty IM3 prepaid card. This study aimed to determine the effect of product quality, image and brand to the customer loyalty through satisfaction. The hypothesis stated that the quality (X1),image (X2) and brand (X3) have significant influence to the customer loyalty (Y) through satisfaction (Z). This type of research is explanatory research. The data used in this study is primary data obtained using questionnaires and library research. The population in this study were all students of the Faculty of Social and Political Sciences with a sample of 100 respondents using accidental sampling technique. Data analysis techniques used simple linear regression and path analysis using SPSS 16 for windows. Based on the analysis it can be concluded that there is a positive and significant influence between product quality to satisfaction, there is a positive and significant influence between the image to satisfaction, there is a positive and significant influence between brand to the satisfaction, there is a positive and significant influence between product quality, brand and image to satisfaction, there is a positive and significant influence between product quality to loyalty, there is a positive and significant influence between image to loyalty, there is a positive and significant influence between brand to loyalty, there is a positive and significant influence between the quality of the product, image and brand to loyalty, there is the significant influence of satisfaction to loyalty. We suggest is the company must improve the quality of IM3, especially in terms of access to internet services, add and improve the network so that customers do not feel disturbed, introduce more card advantage that people get to know IM3 products.